The Use of Technology as a Learning Medium for Young Learners: An Effort to Enhance Children's Engagement and Understanding - Lailatus Sa'adah; Briel Leva Yebi; Marlina Yupitasari (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
The rapid growth of digital technology has significantly impacted the educational landscape, particularly in language learning for young learners. This study aims to explore the use of digital media as a learning tool to enhance engagement and understanding in English language acquisition. A literature review methodology was employed to gather and analyze data from relevant studies, including journal articles, books, and research reports published between 2021-2024. The findings suggest that interactive digital platforms, such as YouTube, TikTok, and educational apps like Canva and Wordwall, play a crucial role in fostering language skills, increasing motivation, and supporting independent learning among young bilingual learners and Generation Z students. These digital tools not only facilitate language learning but also contribute to character development and the reinforcement of affective values. Additionally, the research highlights the effectiveness of these technologies in creating an engaging and flexible learning environment, which is particularly relevant in post-pandemic contexts and areas with limited resources. The study concludes that the integration of digital media in English language education is vital for creating a dynamic, student-centered learning experience, making it an essential component of contemporary educational strategies